Proposal for an index of access and ownership of ICT in Public Educational Centers in Costa Rica - Valverde-Hernández, Melissa Edith; Paniagua-Esquivel, Cristina (Innovaciones Educativas, 2021)
This article presents a proposal for an index of access and ownership of technologies in educational centers, to quantify the existing gap between them. Two indicators are proposed: access and possession of digital technology to build the ICT Access and Tenure Index (IAT TIC). After the design of the index, it will be applied to the data of the I National Census of Digital Technologies in Education, carried out by the Ministry of Public Education of Costa Rica in collaboration with the University of Costa Rica. This census includes the data of 3733 educational centers. The results include lower average magnitudes such as Sulá (2.5) and Coto (4.19) and higher ones in central regions of the country. Therefore, it is concluded that the IAT-ICT is a consistent index, which quantifies a gap in access and possession of ICT in Costa Rican public educational centers.